Positioning childcare matters among working mothers / Zakirah Zaid,Suhaida Mohd Amin and Abd Halim Mohd Noor - Zaid, Zakirah; Mohd Amin, Suhaida; Mohd Noor, Abd Halim (Universiti Teknologi MARA Cawangan Kelantan, 2020)
The involvement of females in the labor market nowadays has become vital to fulfill the demand from organizations. This paper discusses the factors that relate to childcare that affects mothers’ involvement in the labor market. The availability of childcare influences the participation of mothers in the labor force. There are some areas that are difficult to find childcare places that can give satisfaction to mothers because they are in an isolated area. Next, the quality of childcare becomes a priority for parents nowadays to ensure their children’s safety. Recently, parents have started to be more alert about the education offered by childcare services because they prefer their children to learn at an early age. This means that, in addition to childcare, the educational aspect is important. In addition, the accessibility of ch ildcare is also important because there are areas that are inaccessible to childcare centers due to certain circumstances. However, all the aspects potentially increase the childcare fees, resulting in the service becoming more expensive. The high cost of care will increase the financial burden on low-income parents. For that reason, there are mothers who are willing to forgo their careers to take care of their children. However, to what extent do the above issues really relate to working mothers in Malaysia? Therefore, the objective of this paper is to review the factors related to childcare matters that influence Malaysian mothers’ participation in the labor force